Characteristics of Innovation Affecting Adopted Decision on Sufficiency Economy Philosophy in People’s Way of Lives in Muen Wai Sub-district, Nakhon Ratchasima Province - Wichian, Anyarat; Untong, Akarapong (Journal of Business, Innovation and Sustainability (JBIS), 2023)
The objectives of this article was to study the influence of innovation characteristics on decision making in applying the Sufficiency Economy Philosophy to people’s way of lives in Muen Wai Sub-district, Nakhon Ratchasima Province by applying the binary logistic regression model to analyze the data from interviews 291questionnaires. The results of the study found that the cha-racteristics of innovation, which consisted of observing others to apply the Sufficiency Economy Philosophy, the compatibility of the Sufficiency Economy Philosophy and people’s way of lives as well as the trialability of the Sufficiency Economy Philosophy, is a characteristic that influences adopted decision on the Sufficiency Economy Philosophy in people’s way of lives. From the results of such study, there is an importance suggestion that the relevant agencies should also formulate guideline for promoting the application of the Sufficiency Economy Philosophy on the basis of its characteristics, such as applying the Sufficiency Economy Philosophy to what the villagers already have had, supporting and encouraging individuals to attend training with emphasis and pay attention to training that shall be done in practice, and supporting role models of the Sufficiency Economy Philosophy, etc.